(untitled) (The Review of Diabetic Studies, 2025)
Background: Laboratory systems are a critical component of health security, enabling timely detection, diagnosis, and monitoring of infectious diseases and public health threats. In low-resource settings, laboratory capacities are often limited by inadequate infrastructure, insufficient workforce training, fragmented supply chains, and weak quality management systems. Strengthening laboratory systems is therefore essential for improving health security preparedness and response. Objectives: This systematic review aims to identify and synthesize evidence on effective models and strategies for strengthening laboratory systems in low-resource settings, with a focus on interventions that enhance diagnostic capacity, quality management, workforce competency, and integration into health security frameworks. Methods: A systematic search of PubMed, Embase, Scopus, and Web of Science was conducted for studies published between January 2000 and December 2025. Eligible studies evaluated interventions, programs, or models aimed at improving laboratory systems in low-resource contexts. Data were extracted on study design, intervention type, setting, outcomes, and impact on health security. Due to heterogeneity in study designs and outcome measures, findings were synthesized narratively. Results: A total of 1,132 records were identified, of which 42 studies met the inclusion criteria. Key strategies associated with successful laboratory strengthening included workforce development and training programs, implementation of quality management systems, establishment of tiered laboratory networks, integration of laboratory information systems, and adoption of standardized protocols for biosafety and diagnostic workflows. Multi-component interventions that combined training, infrastructure improvement, and mentorship demonstrated the greatest impact on diagnostic accuracy, turnaround time, and system resilience. Several studies also highlighted the importance of partnerships between local institutions, international agencies, and non-governmental organizations to support sustainable laboratory capacity building. Conclusion: Strengthening laboratory systems in low-resource settings is essential for effective health security and disease outbreak response. Evidence suggests that multi-component, context-adapted interventions that combine workforce development, quality management, infrastructure enhancement, and system integration are most effective. Future research should focus on standardized metrics to evaluate laboratory system performance and on scalable models that can be adapted across diverse low-resource settings.